Prospects for the development of an effective immunological method for the control of African trypanosomiasis - Nantulya, V.M.; Musoke, A.J. (Ahmadu Bello University, 1982)
Discusses prospects for the Development of a vaccine against African trypanosomiasis & dissemination of genetically resistant breeds of livestock into tsetse-infected areas of the continent; reviewing the various approaches being pursued for vaccine Development, viz. induction of immunity by use of non-specific immunostimulants; and vaccination using surface antigens, plasma membrane antigens & sub-cellular fractions of trypanosomes and tacyclic antigens, and outlining the need to conduct research on the phenomenon of trypanotolerance.